Treatment and control of hypertension in Turkish population: a survey on high blood pressure in primary care (the TURKSAHA study) - (:unkn) unknown (NATURE PUBLISHING GROUP, 2006)
Although the management and the control rates of hypertension are generally low throughout the world, there are substantial differences between the countries. The aim of this study was to determine the control rate of blood pressure and the characteristics of the patients who have been admitted to primary care units in Turkey. Our study included 16 270 patients aged above 18 years who were diagnosed as hypertensive in representative nationwide sample of 1000 primary care units in Turkey. The mean age of the patients was 60 +/- 11 years (60.1% women). Of 16270 patients, 15187 (93.3%) were on an antihypertensive treatment, whereas 1083 (6.7%) were receiving no treatment. The patients who were women, diabetic, smoker, obese, and those who had a concomitant cardiovascular disease (CVD) had a higher rate of antihypertensive treatment. Of 15187 treated patients, 4912 (30.2%) had a controlled systolic blood pressure, 7063 (43.4%) a controlled diastolic blood pressure, and in 3931 (24.2%), both were under control. A logistic regression analysis demonstrated that age (OR 1.33), diabetes (OR 4.96), body mass index (OR 1.41) and the presence of a CVD (OR 1.19) were predictors for blood pressure being under control. The blood pressure control rates ranged between 16.6 and 30.5% among seven geographical regions. In the primary care units in Turkey, the blood pressure control rate is consistently low in treated hypertensive patients. In addition, there are differences between the geographical regions in both the proportion of those receiving medications and the blood pressure control rates.
Keywords: primary; care; Turkey; UNITED-STATES; PREVALENCE; MANAGEMENT; COMMUNITY; AWARENESS; CANADA